CD90 is not constitutively expressed in functional innate lymphoid cells - Schroeder, Jan-Hendrik; Beattie, Gordon; Lo, Jonathan W.; Zabinski, Tomasz; Powell, Nick; Neves, Joana F.; Jenner, Richard G.; Lord, Graham M. (Frontiers in Immunology, 2023)
Huge progress has been made in understanding the biology of innate lymphoid cells (ILC) by adopting several well-known concepts in T cell biology. As such, flow cytometry gating strategies and markers, such as CD90, to identify ILC have been applied. Here, we report that most non-NK intestinal ILC have a high expression of CD90 as expected, but surprisingly a sub-population of cells exhibit low or even no expression of this marker. CD90-negative and CD90-low CD127+ ILC were present amongst all ILC subsets in the gut. The frequency of CD90-negative and CD90-low CD127+ ILC was dependent on stimulatory cues in vitro and enhanced due to dysbiosis in vivo. CD90-negative and CD90-low CD127+ ILC were a potential source of IL-13, IFNγ and IL-17A at steady state and upon dysbiosis- and dextran sulphate sodium-elicited colitis. Hence, this study reveals that, contrary to expectations, CD90 is not constitutively expressed by functional ILC in the gut.